Construction of Audit Evaluation Index System of Targeted Poverty Alleviation Based on AHP - Changping Yin, Junhan Yang, Xiaojiao Bai, Li Zhong (Forest Chemicals Review)
In recent years, the state and regions have invested a large number of special funds in poverty alleviation. Based on combing relevant literature, the audit evaluation index system of targeted poverty alleviation was constructed from two dimensions: the process and the benefit of poverty alleviation. And the weight of each index was determined by AHP. Then, taking Z county as an example, the field application is carried out to revise the audit evaluation index system of targeted poverty alleviation. It is better to promote the development of targeted poverty alleviation and elimination smoothly.